2012
DOI: 10.1038/ncomms1752
|View full text |Cite
|
Sign up to set email alerts
|

FAT10 and NUB1L bind to the VWA domain of Rpn10 and Rpn1 to enable proteasome-mediated proteolysis

Abstract: FAT10 is the only ubiquitin-like modifier that can target proteins for degradation by the proteasome in a ubiquitin-independent manner. The degradation of FAT10-linked proteins by the proteasome is strongly accelerated by the ubiquitin-like-ubiquitin-associated protein nEDD8 ultimate buster-1 long (nuB1L). Here we show how FAT10 and nuB1L dock with the 26s proteasome to initiate proteolysis. We identify the 26s proteasome subunit hRpn10/s5a as the receptor for FAT10, whereas nuB1L can bind to both Rpn10 and Rp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 49 publications
9
87
0
Order By: Relevance
“…For example, the NUB1 (Nedd8 ultimate buster-1), a Nedd8-interacting protein, can interacts with hRpn10/S5a subunit of 26S proteasome and function as an adaptor between Nedd8 and hRpn10. In this manner, NUB1 recruits Nedd8 and Nedd8-conjugated proteins to the proteasome for degradation independent of ubiquitylation [57][58][59][60] . Therefore, we cannot rule out the possibility that NUB1 and Nedd8 work together to downregulate the expression levels of Smurf1 and its substrates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the NUB1 (Nedd8 ultimate buster-1), a Nedd8-interacting protein, can interacts with hRpn10/S5a subunit of 26S proteasome and function as an adaptor between Nedd8 and hRpn10. In this manner, NUB1 recruits Nedd8 and Nedd8-conjugated proteins to the proteasome for degradation independent of ubiquitylation [57][58][59][60] . Therefore, we cannot rule out the possibility that NUB1 and Nedd8 work together to downregulate the expression levels of Smurf1 and its substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these proteins did not belong to distinct cellular pathways but covered a lot of different cellular functions, showing that FAT10 might play a role in numerous cell biological processes Leng et al, 2014). Of importance is that FAT10 apparently is not only functional when covalently conjugated to its substrate proteins, such as the ubiqui-tin activating enzyme UBE1 (Bialas et al, 2015;Rani et al, 2012), but also when interacting non-covalently with interaction partners such as HDAC6 (Kalveram et al, 2008), aryl-hydrocarbon receptor like-1 (AIPL1), an important protein within the retina (Bett et al, 2012), or the autophagosomal receptor p62/SQSTM1 which interacts both, covalently and non-covalently with FAT10 . Activation and conjugation of FAT10 to its substrate proteins is performed most probably by a three step enzymatic cascade, as described for ubiquitin.…”
Section: Which Are the Targets Of Fat10 And How Is It Conjugated To Imentioning
confidence: 99%
“…NUB1L, a likewise interferon-inducible protein (Kito et al, 2001), acts as a soluble receptor and brings FAT10 and FAT10ylated proteins to the proteasome where it binds to the 19S regulatory subunits RPN10 (S5a) and RPN1 (S2). It was shown that FAT10 itself could also directly bind to the VWA domain of RPN10 in the absence of NUB1L but that the docking of NUB1L to the proteasome was necessary for the accelerated degradation of FAT10 (Rani et al, 2012;Schmidtke et al, 2009Schmidtke et al, , 2006. In contrast to ubiquitin, FAT10 has a very short half life of about 1 h and seems to be degraded by the proteasome along with its substrates Hipp et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it was not addressed whether the enhanced FAT10-induced antigen presentation is dependent on poly-FAT10ylation. However, in a different study, not addressing antigen presentation, FAT10 with its two ubiquitin-like domains served as a degradation signal with no need for chain formation (Rani et al, 2012). Rpn10 knockdown was associated with a significantly impaired pp65 495-503 epitope presentation from the FAT10-pp65 fusion protein, indicating that docking of FAT10 to the 26S proteasome occurs via Rpn10 (Ebstein et al, 2012).…”
Section: Fat10 In Antigen Processingmentioning
confidence: 97%
“…To initiate proteolysis both FAT10 and NUB1L dock to the 26S proteasome. Docking of FAT10 to the 26S proteasome occurs via the VWA domain of the 19S cap of the 26S proteasome subunit Rpn10 (S5a), whereas NUB1L can bind to both 19S cap subunits Rpn10 and Rpn1/S2 (Rani et al, 2012). Hence, in principle, FAT10 is able to target potential antigens for proteasomal degradation.…”
Section: Fat10 In Antigen Processingmentioning
confidence: 99%